Stability of salivary microRNA measures across an NCAA Division I football season: implications for microRNA as a biomarker of concussion - Campbell, T. R.; Zamponi, M.; Leathers, D.; Cavallario, J.; Martinez, J. C.; Mollica, P. A. (PLOS ONE, 2026)
Background: Clinicians often face challenges in concussion care due to a heavy reliance on subjective patient input. Recently, research has sought objective biomarkers, like salivary microRNAs, to improve concussion management. However, significant limitations hinder the use of microRNAs as a diagnostic tool, including the cumulative effects of a contact sport season. A better understanding of the response to a contact sport season would help researchers and clinicians interpret expression changes at the time of injury in the context of seasonal variation. in Therefore, this study investigated the reliability of previously identified salivary microRNA targets across one contact sport season.